1993
DOI: 10.1073/pnas.90.21.10061
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic disease induced in transgenic mice by cerebral overexpression of interleukin 6.

Abstract: Cytokines are thought to be important mediators in physiologic and pathophysiologic processes affecting the central nervous system (CNS). To explore this hypothesis, transgenic mice were generated in which the cytokine interleukin 6 (IL-6), under the regulatory control of the glial fibrillary acidic protein gene promoter, was overexpressed in the CNS. A number of transgenic founder mice and their offspring exhibited a neurologic syndrome the severity of which correlated with the levels of cerebral IL-6 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
669
3
11

Year Published

1998
1998
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 925 publications
(744 citation statements)
references
References 36 publications
49
669
3
11
Order By: Relevance
“…Glial fibrillary acidic protein (GFAP)-IL-6 transgenic mice overexpressing IL-6 selectively in astrocytes 14 were a generous gift from Iain L. Campbell, The Scripps Research Institute, La Jolla, CA. VEGF-green fluorescent protein (GFP) mice carrying the reporter gene GFP under the control of the VEGF promoter 28 were contributed generously by Brian Seed, Massachusetts General Hospital, Boston, MA.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Glial fibrillary acidic protein (GFAP)-IL-6 transgenic mice overexpressing IL-6 selectively in astrocytes 14 were a generous gift from Iain L. Campbell, The Scripps Research Institute, La Jolla, CA. VEGF-green fluorescent protein (GFP) mice carrying the reporter gene GFP under the control of the VEGF promoter 28 were contributed generously by Brian Seed, Massachusetts General Hospital, Boston, MA.…”
Section: Animalsmentioning
confidence: 99%
“…To study the transcriptional regulation of VEGF by IL-6 in vivo, we used GFAP-IL-6 transgenic mice overexpressing IL-6 in astrocytes 14 and crossbred them with VEGF-GFP reporter mice carrying the reporter gene GFP under the control of the human VEGF promoter. 28 In VEGF promoter activation, GFP is expressed and can be visualized in coronal sections using a fluorescence microscope.…”
Section: Il-6 Induces Vegf Transcription In the Mouse Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Such alterations could presumably make an important contribution to the clinicopathological features of many neurological disorders, but the possibility that they are simply the consequence and not the cause must be ruled out experimentally. Results obtained in transgenic mice with astrocyte-targeted expression of cytokines such as IL-6 (5,6,8,12,14,31,52,60), IL-3 (13), IFN-␣ (1), and TNF-␣ (59) have unequivocally demonstrated that an abnormal cytokine production has the potential to cause devastating neurological disorders. Interestingly, each of these cytokines caused a specific repertoire of clinicopathological sequelae that presumably reflect the unique actions of the particular cytokine expressed.…”
Section: Introductionmentioning
confidence: 99%
“…Histological findings included astrocytosis, angiogenesis and neuro-degeneration. 28 IL-6 deficient (−/−) mice are resistant to myelin oligodendrocyte glycoprotein (MOG)-induced EAE. 29,30 This is not for lack of encephalitogenic cells as transfer of IL-6 +/+ T cells cannot induce disease consistent with IL-6 functioning at the perivascular inflammatory process.…”
Section: Immunotherapies Of Eaementioning
confidence: 99%